Perancangan UI/UX pada Aplikasi Financial Technology ARENA - Aditya Dava Samsudin; Brian Nur Ardiansyah; Didi Juardi; Jovita Larasati Poetri (Jurnal Ilmiah Wahana Pendidikan, 2023)
This article was created to explain the design of the User Interface & User Experience design on a Financial Technology application called ARENA Investasi. This design is the final project of a Binar Academy Bootcamp, this design was made using Figma, Miro software, and other design and brainstorming applications to carry out this design to completion. This article uses qualitative and descriptive research methods to describe the process, design results and is written based on the conditions and situations of the designed subject